Safety and Efficacy of PTH 1‐34 and 1‐84 Therapy in Chronic Hypoparathyroidism: A Meta‐Analysis of Prospective Trials. (20th May 2022) - Puliani, Giulia; Hasenmajer, Valeria; Simonelli, Ilaria; Sada, Valentina; Pofi, Riccardo; Minnetti, Marianna; Cozzolino, Alessia; Napoli, Nicola; Pasqualetti, Patrizio; Gianfrilli, Daniele; Isidori, Andrea M.
ABSTRACT: Hypoparathyroidism is the only endocrine deficiency for which hormone replacement therapy is not the standard of care. Although conventional treatments may control hypocalcaemia, other complications such as hyperphosphatemia, kidney stones, peripheral calcifications, and bone disease remain unmet needs. This meta‐analysis (PROSPERO registration number CRD42019126881) aims to evaluate and compare the efficacy and safety of PTH1−34 and PTH1−84 in restoring calcium metabolism in chronic hypoparathyroidism. EMBASE, PubMed, and CENTRAL databases were searched for randomized clinical trials or prospective studies published between January 1996 and March 2021. English‐language trials reporting data on replacement with PTH1−34 or PTH1−84 in chronic hypoparathyroidism were selected. Three authors extracted outcomes, one author performed quality control, all assessed the risk of biases. Overall, data from 25 studies on 588 patients were analyzed. PTH therapy had a neutral effect on calcium levels, while lowering serum phosphate (−0.21 mmol/L; 95% confidence interval [CI], −0.31 to −0.11 mmol/L; p < 0.001) and urinary calcium excretion (−1.21 mmol/24 h; 95% CI, −2.03 to −0.41 mmol/24 h; p = 0.003). Calcium phosphate product decreased under PTH1−84 therapy only. Both treatments enabled a significant reduction in calcium and calcitriol supplementation. PTH therapy increased bone turnover markers and lumbar spine mineral density. Quality of life improved and there was no difference in the safety profile between PTH and conventionally treated patients. Results for most outcomes were similar for the two treatments. Limitations of the study included considerable population overlap between the reports, incomplete data, and heterogeneity in the protocol design. In conclusion, the meta‐analysis of data from the largest collection to date of hypoparathyroid patients shows that PTH therapy is safe, well‐tolerated, and effective in normalizing serum phosphate and urinary calcium excretion, as well as enabling a reduction in calcium and vitamin D use and improving quality of life. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).